Site and Nationalism: The Significant Value of Liangan Site in History Learning (Paramita: Historical Studies Journal, 2021)
Indonesia is vulnerable to facing threats related to national disintegration. It is important for us to present various forms of cultural objects that have noble, togetherness and moral values, in order to maintain the unity and integrity of the nation. The purpose of this study is to determine the importance of Liangan Site as a cultural object to increase a sense of nationalism in history learning. This research was conducted using a mixed method with a sequential explanatory approach. The results showed that Liangan Site had the potential issue to increase a sense of nationalism with a percentage of 76.4%. The results of this study indicate that Liangan Site as a cultural object has the potential to increase a sense of nationalism. Utilization of Liangan Site in learning activities can dig deeper into their imagination about the life of Liangan community in the past. The existence of Liangan Site encourages a sense of pride in students. In this study, it was found that Liangan as a historical site should be utilized as a learning resource with supporting public facilities so that visitors feel comfortable to stay. Liangan Site is expected to become a part of the materials for the development of Hindu-Buddhist Kingdom in Indonesia in History Subject in the first semester of Class X as it has a significant value for the development of the Ancient Mataram Kingdom.Indonesia rentan menghadapi ancaman terkait disintegrasi bangsa. Penting bagi kita untuk menghadirkan berbagai bentuk benda budaya yang memiliki nilai luhur, kebersamaan dan moral, demi menjaga persatuan dan kesatuan bangsa. Tujuan dari penelitian ini adalah untuk mengetahui pentingnya Situs Liangan sebagai objek budaya untuk meningkatkan rasa nasionalisme dalam pembelajaran sejarah. Penelitian ini dilakukan dengan menggunakan metode campuran dengan pendekatan sekuensial explanatory. Hasil penelitian menunjukkan bahwa Situs Liangan memiliki potensi isu untuk meningkatkan rasa nasionalisme dengan persentase sebesar 76,4%. Hasil penelitian ini menunjukkan bahwa Situs Liangan sebagai objek budaya berpotensi meningkatkan rasa nasionalisme. Pemanfaatan Situs Liangan dalam kegiatan pembelajaran dapat menggali lebih dalam imajinasi mereka tentang kehidupan masyarakat Liangan di masa lalu. Keberadaan Situs Liangan mendorong rasa bangga pada siswa. Dalam penelitian ini ditemukan bahwa Liangan sebagai situs sejarah harus dimanfaatkan sebagai sumber belajar dengan fasilitas umum yang mendukung agar pengunjung merasa nyaman untuk menginap. Situs Liangan diharapkan dapat menjadi bagian dari materi pengembangan Kerajaan Hindu-Budha di Indonesia pada Mata Pelajaran Sejarah pada semester I Kelas X karena memiliki nilai yang signifikan bagi perkembangan Kerajaan Mataram Kuno.